PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM PEMBELAJARAN - Herdyanto, Herdyanto; Feizal, Muhammad (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Data and Information Technology Center of the Ministry of Education, Culture, Research, and Technology on its website informs that the integration of information and communication technology into the learning process is needed to develop students' high-level thinking skills, develop skills in the field of Technology, and to improve the effectiveness, efficiency and attractiveness of the learning process. However, the use of Information and Communication Technology (ICT) and its devices in the world of education, especially in Indonesia, is often less than optimal, for example it is only used to assist administrative activities in schools. Therefore, teachers as drivers of education are expected to have sufficient skills and competencies to utilize existing ICT so that it is more optimal in delivering lesson materials in schools and for other learning activities. Based on this, SDN Keroncong 1 strives to prepare teachers to have sufficient skills and competencies that are not only beneficial for teachers themselves in the use of ICT but are expected to indirectly have an impact on improving the quality of students. Kata kunci: ICT, Education, Learning, SDN Keroncong 1